Analysis of the Implementation of the E-Puskesmas Application Usage (Case Study: Puskesmas Pauh in Padang City) - Lathivolya. R, Novrilla; Muslim, Burhan; Fadhilatul Hasnah (CV. CENDIKIA JENIUS INDONESIA, 2025)
E-Puskesmas is an electronic-based management information system designed to enhance the efficiency and quality of services in community health centers (Puskesmas). The low visit rate at Puskesmas Pauh indicates an ineffectiveness in the implementation of the e-Puskesmas application. This study aims to analyze the implementation of the e-Puskesmas application at Puskesmas Pauh. A qualitative research method with a case study approach was employed, conducted from March to August 2025 at Puskesmas Pauh through interviews, document reviews, and observations. Informants were selected using purposive sampling, totaling seven individuals. Data analysis utilized technique triangulation and source triangulation. The results revealed limitations in human resources, network infrastructure, and hardware. Additionally, the lack of a specific standard operating procedure (SOP) for e-Puskesmas constituted a major obstacle to effective application usage. Technical disruptions, particularly network instability, resulted in slow service delivery. However, the application has successfully supported rapid and accurate reporting in the Integrated Reporting and Management System for Puskesmas (SP2TP) within the Health Office. In conclusion, the implementation of e-Puskesmas at Puskesmas Pauh still faces challenges from both technical aspects and human resources. It is recommended that the health center enhance the capacity of its personnel and technological infrastructure to optimize the effectiveness of this application.